Licorice extract/gellan gum aerated gels: Insights into structure and properties - Mehdi Varidi; Fatemeh Alkobeisi; Majid Nooshkam (Food Chemistry: X)
The incorporation of dispersed air in gel-type foods can meet the new textural and functional demands. The present study was therefore conducted to create aerated gels using gellan gum (GelG; 0.7, 1, and 1.3 % w/v) and licorice root extract (LRE; 0.4, 0.7, and 1 % w/v) through cold-induced ionic gelation. The gels were characterized using Fourier transforms infrared spectroscopy and X-ray diffraction to confirm the interaction between the components. The aerated gels had an overrun of up to 156.04 %, porosity of up to 60.81 %, and a water holding capacity of approximately 100 %. Additionally, the elastic characteristics (G′) were more prominent than the viscous ones (G′′), suggesting that the gels exhibit solid-like behavior. The calcium release from the aerated gels significantly increased by approximately 16 % as a function of GelG concentrations. The aerated gels with high overrun, stability, and viscoelasticity can be used to design novel low-calorie and healthy aerated foods.